Case Report: Diagnosis and treatment of an undifferentiated embryonal sarcoma of the liver - Xiaojiao Qiu; Lexing Zhang; Fan Sun (Frontiers in Surgery)
Undifferentiated embryonal sarcoma of the liver (UESL) is an exceedingly rare primary malignant tumor, predominantly affecting children and, to a lesser extent, adults. In adult patients, UESL constitutes a mere 7% of all liver sarcomas. This case report details an instance of hepatic embryonal sarcoma in a 33-year-old female patient who had no significant prior medical history and presented with complaints of abdominal pain. She was hospitalized for surgical intervention. Diagnostic imaging, including CT and MRI scans, disclosed a substantial cystic mass located in the right lobe of the liver. A lumpectomy was performed, and subsequent pathological and histological examinations confirmed the diagnosis of undifferentiated embryonal sarcoma. After surgery, the patient received adjuvant chemotherapy. We are pleased to report that she has remained in complete and sustained remission for the past 3 years.